Behavioural determinants of financial risk tolerance: Evidence from Malaysia / Md Mahfuzur Rahman - Md Mahfuzur , Rahman (2015)
Financial risk tolerance is one of the fundamental inputs of investment management models and it differs among individuals. Past studies on this topic have focused mainly on background analysis particularly demographic characteristics. However, there have not been many empirical data that analyse why financial advisors fail to accurately assess financial risk tolerance and guide individuals despite of knowing the demographic characteristics. To address the shortcomings of the instruments used by financial advisors to assess and guide individuals, this study extensively synthesises related literature in other disciplines such as psychology, behavioural economics, and behavioural finance. Research in the psychology, behavioural economics and behavioural finance contexts have identified behavioural propensities as promising behavioural factors to overcome such limitations. Therefore, behavioural propensities literatures are reviewed, analysed, synthesised to improve the understanding on the assessment of individuals’ financial risk tolerance and what other factors beyond individuals’ demographic characteristics, should be also assessed. To achieve this aim, this study investigates the influence of six (6) core behavioural factors (such as propensity for regret, propensity for trust, happiness in life, propensity to attribute success to luck, propensity for overconfidence, propensity for social interaction) on financial risk tolerance. This study also examines whether the levels of financial risk tolerance and behavioural propensities significantly differ among the gender and ethnic groups. In addition, the study analyses the role of religiosity and ethnicity in the relationship between behavioural factors (behavioural propensities) and financial risk tolerance. Empirical data were collected using a survey questionnaire. The questionnaires were distributed to the Malaysian undergraduate students based on quota sampling method to confirm the representativeness of the targeted population. A total of 1679 questionnaires were distributed to six public universities in the Klang Valley. However only 1204 questionnaires were completed and used for analysis. This study employs structural equation modelling to validate and assess proposed research model. The results of the analysis demonstrated some new findings. First, the findings indicate that propensity for regret, propensity for trust, happiness in life, propensity to attribute success to luck and propensity for overconfidence have significant influence on financial risk tolerance while propensity for social interaction does not. Second, this study finds significant differences in behavioural propensities and financial risk tolerance among gender and ethnic groups. Lastly, the findings provide support for the moderating effects of religiosity and ethnicity in the proposed research model. Several implications emerge from these findings. The results highlights the important role of behavioural determinants to assess individuals’ financial risk tolerance which in turn highlights the important role of behavioural factors as tools that can be used by financial advisors in ensuring appropriate advice is delivered to clients. Understanding financial risk tolerance is a complex process that goes beyond the exclusive use of demographic characteristics and behavioural factors. Thus, more research is clearly needed to resolve which additional factors can be used by financial advisors to increase the explained variance in financial risk tolerance differences.